2009
DOI: 10.1246/cl.2009.1094
|View full text |Cite
|
Sign up to set email alerts
|

Conformation-dependent Room-temperature Emission Spectra of Single MEH-PPV Chains in Different Polymer Matrices

Abstract: Emission spectra of single molecules of the conjugated polymer MEH-PPV in host matrices of ZEONEX Ò and polystyrene are reported. Depending on the matrix, the polymer chains attain different conformations, from compact defect cylinders to extended defect coils. The conformations are correlated with photophysical properties, such as emission intensity fluctuations, and with shapes and peaks of emission spectra. The observed bimodal distribution of the spectral peaks is related to distribution in conjugated segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 20 publications
(25 reference statements)
2
22
0
Order By: Relevance
“…Single MEH-PPV chains (M W~2 00 kDa) have been studied by different techniques of single-molecule spectroscopy at a temperature of T = 1.2 K. We have found a bimodal distribution of emission maxima as reported before [19,24,[42][43][44][45][46][47] and have addressed the question as to the nature of the red subpopulation of emitters. The fact that no qualitative difference could be revealed in emission spectra, fluorescence excitation spectra and the fluorescence decay behaviour has led us to the conclusion that the red sites are to be attributed to longer chromophoric units rather than interactions between chromophores (supposedly resulting in excimers or aggregates).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Single MEH-PPV chains (M W~2 00 kDa) have been studied by different techniques of single-molecule spectroscopy at a temperature of T = 1.2 K. We have found a bimodal distribution of emission maxima as reported before [19,24,[42][43][44][45][46][47] and have addressed the question as to the nature of the red subpopulation of emitters. The fact that no qualitative difference could be revealed in emission spectra, fluorescence excitation spectra and the fluorescence decay behaviour has led us to the conclusion that the red sites are to be attributed to longer chromophoric units rather than interactions between chromophores (supposedly resulting in excimers or aggregates).…”
Section: Discussionsupporting
confidence: 52%
“…Using a sufficiently short excitation wavelength, the distribution is characterised by the bimodal behaviour (Figure 1 a, l exc = 514 nm, 54 molecules studied), repeatedly reported in the literature for MEH-PPV. [19,24,[42][43][44][45][46][47] It was fitted with a combination of two Gaussians with maxima of 18 230 cm À1 and 16 570 cm À1 and full widths at half-maximum (fwhm) of 1100 cm À1 and 1020 cm À1 . An excitation wavelength of l exc = 568 nm resulted in a monomodal distribution of emission maxima, because only the red subpopulation was accessible under these conditions (255 molecules studied).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[28][29][30][31][32][33][34][35][36][37] Recent work by three of us 27 showed that MEH-PPV chains dissolved in methyltetrahydrofuran (MeTHF) undergo a phase transition at approximately 200 K. Above this temperature, the polymer exists in a disordered coil morphology referred to as the blue phase. As the solution is cooled through the transition temperature, the polymer assembles into aggregates (the "red-phase") in which polymer chains are substantially elongated causing a red shift of the absorption and fluorescence spectra relative to the spectra of more disordered chains.…”
Section: Introductionmentioning
confidence: 99%